Biomarker Guided Diagnosis of Septic Peritonitis in Dogs - Martiny, Pia; Goggs, Robert (Frontiers in Veterinary Science, 2019)
Septic peritonitis (SP) is common in dogs and is associated with high mortality. Early recognition is essential to maximizing survival and may be aided by biomarker measurement. The present study aimed to evaluate the ability of biomarkers to discriminate septic from non-septic ascites (NSA). Eighteen dogs with SP and 19 age-matched controls with NSA were enrolled. Contemporaneous blood and peritoneal effusion samples were obtained. Concentrations of cell-free DNA (cfDNA), cytokines, glucose, lactate, N-terminal pro-C-type natriuretic peptide (NT-proCNP), nucleosomes, and procalcitonin (PCT) were measured using commercial reagents and assays. Paired biomarker concentrations were compared with the Wilcoxon matched-pairs signed rank test, and biomarker concentrations between groups were compared with the Mann-Whitney U test. P-values were adjusted for multiple comparisons using the Bonferroni correction. Receiver operating characteristic curves were generated to assess the ability of the above biomarkers to discriminate SP from NSA. Dogs with SP had significantly greater blood CCL2 concentrations than dogs with NSA (P=0.032). Dogs with SP had significantly greater effusion CCL2, IL-6, IL-10 and lactate concentrations than dogs with NSA (P0.0121). Blood-effusion concentration gradients of CCL2, glucose, IL-6, IL-10, and lactate were significantly different in dogs with SP compared to dogs with NSA (P0.0165). Effusion lactate concentration had the highest AUROC value (0.866, 95% CI 0.751-0.980, P=0.0001), although other biomarkers performed similarly. An effusion lactate concentration of 4.2 mmol/L was 72.2% (95% CI 46.5-90.3%) sensitive and 84.2% (95% CI 60.4-96.6%) specific for the diagnosis of SP.